Defining a rhombus - Foster, Colin; Hodgen, Jeremy; Küchemann, Dietmar (Association of Teachers of Mathematics, 2018)
Colin Foster, Jeremy Hodgen and Dietmar Kuchemann exlore how the use of examples and counter-examples can support students developing understandings of definitions.